The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acs.jafc.8b00550
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Starch with Low Retrogradation Properties Produced by Modification of the GtfB Enzyme 4,6-α-Glucanotransferase from Streptococcus thermophilus

Abstract: A GtfB enzyme 4,6-α-glucanotransferase from Streptococcus thermophilus lacking 761 N-terminal amino acids was heterologously expressed in Escherichia coli. Purified S. thermophilus GtfB showed transglycosylation activities toward starch, resulting in branch points of (α1→6)-glycosidic linkages plus linear chains of (α1→4)-glycosidic linkages. After wheat starch was modified at a rate of 0.1 g/mL by 1-4 U/g starch GtfB at pH 6.0 and 40 °C for 1 h, the weight-averaged molecular weight decreased from 1.70 × 10 g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 49 publications
1
32
0
2
Order By: Relevance
“…Such modification evidently increases the branching density and increases the relative content of short AP chains (DP < 12). It also lowers the extent of retrogradation upon storage at 4 • C (Li, Fei, et al, 2018). Unfortunately, the impact on starch digestion has not been studied.…”
Section: Shortening Of Ap Chains and Increasing Branching Densitymentioning
confidence: 99%
“…Such modification evidently increases the branching density and increases the relative content of short AP chains (DP < 12). It also lowers the extent of retrogradation upon storage at 4 • C (Li, Fei, et al, 2018). Unfortunately, the impact on starch digestion has not been studied.…”
Section: Shortening Of Ap Chains and Increasing Branching Densitymentioning
confidence: 99%
“…MMP-2 and MMP-9, which are key factors in cancer metastasis, were affected by RBP4 overexpression. This suggested that RBP4 stimulates cancer cell migration along with cell proliferation [28]. Overall, RBP4 could be a negative factor in the response to MSC transplantation, although it is related to cell migration in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…4,6-α-GTs may find application in the fields of the synthesis of dietary fiber, ,, antiretrogradation of starch, , and synthesis of oligosaccharides with the function of immune regulation . In the past decade, only 10 4,6-α-GTs have been characterized, and the catalytic mechanism explaining the products of 4,6-α-GTs with different structures has remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The order of the four motifs in the GtfB-like subfamily sequence is ii−iii−iv−i, which differs from the order of i−ii−iii−iv in the GtfC/D-like subfamily sequence. 4,6-α-GTs may find application in the fields of the synthesis of dietary fiber, 9,14,15 antiretrogradation of starch, 16,17 and synthesis of oligosaccharides with the function of immune regulation. 18 In the past decade, only 10 4,6-α-GTs have been characterized, and the catalytic mechanism explaining the products of 4,6-α-GTs with different structures has remained unclear.…”
Section: Introductionmentioning
confidence: 99%